IMPROVING FINANCIAL ANALYSIS OF ORGANIZATIONS IN ORDER TO PREVENT THEIR INSOLVENCY - V. N. Alferov; E. A. Seredyuk (Модернизация, инновация, развитие, 2015)
The current regulatory analysis of the financial condition of insolvent organizations have some disadvantages also does not account the features of the analysis based on the consolidated financial statements under IFRS and GAAP. In this work on the basis of the comparative analysis of financial condition of a number of large Russian companies, calculated on their accounting statements prepared under Russian accounting standards, IFRS and GAAP, proposals are developed to improve the analysis of financial condition of insolvent institutions.